THE MENTALITY OF THE STAFF IN THE HOTEL INDUSTRY OF RUSSIA - O. Solntseva; М. Mescheryakova (Вестник университета, 2017)
This article presents arguments justifying the need for an integrated impact on the mentality of the Russian people to minimize its negative effect. Three different programs aimed at changing the existing situation on the market were proposed and considered. The expediency of introduction of such innovations is argued.